Siderophore production by Vibrio vulnificus. - Simpson, L M (1983)
Previous studies in our laboratory, as well as clinical evidence, have suggested that increased iron levels in the host may be important in infections caused by the halophilic pathogen Vibrio vulnificus. To study iron acquisition, we induced siderophore production by growth in a low-iron medium, and biochemical testing indicated the production of both hydroxamate- and phenolate-type siderophores. The siderophores were extracted from growth filtrates with ethyl acetate (for phenolates) and phenol-chloroform-ether (for hydroxamates). These extracts enhanced the growth of V. vulnificus when the bacterium was grown in iron-limited medium. The ability of these siderophores to stimulate the growth of Salmonella typhimurium LT-2 enb-7 (a mutant deficient in the biosynthesis of enterochelin) and Arthrobacter flavescens JG-9 (a hydroxamate auxotroph) supported the conclusion that V. vulnificus produces both hydroxamate- and phenolate-type siderophores.